ANALISIS MARKETING LEMBAGA PENDIDIKAN TERHADAP KONSUMERISME JASA PENDIDIKAN - Hikmatul faujiah; Abdul Mu’in Bahaf; Anis Zohriah (Jurnal Genta Mulia, 2024)
In marketing educational services, it is necessary to at least pay attention to aspects of the needs of users and customers of educational services by providing product offerings that suit the people who need them, which is done by processing the marketing of educational services. The purpose of this research is to find out how the marketing mix in educational institutions' marketing affects educational consumerism. This study uses library research methods. The research results show that through the marketing of educational services it is hoped that it will be able to produce satisfaction for students as well as the welfare of educational institution stakeholders. When conducting marketing, you must also highlight the uniqueness of the school so that the public can know the characteristics of the school. The function of marketing in educational institutions is to create a good image of the institution and attract the interest of a number of prospective students. Therefore, marketing must be oriented towards "customers" which in the school context are called students. Marketing of educational services is carried out using a marketing technique known as the 7P marketing mix, namely determining product, price, location, promotion, people, process and physical evidence. physical evidence).